Penggunaan Media Sosial TikTok Dalam Membentuk Persepsi Masyarakat Terhadap Isu Bisnis Agama - M Chairul Aminullah; Indyana Ummi Aisyah; Habibi Rizalul Haq; Rio Kurniawan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study is to determine the use of social media in public perception of religious business issues. The research method used is a literature study by collecting data from various trusted sources on issues relevant to this topic. In the discussion of challenges, it was found that social media is the main problem. Dependence on media owners and political interests influence the content and perspectives of media opinions. In addition, the development of social media and technology also presents new challenges, where public interest in following news programs on social media has decreased. Social media can also be used as a tool for direct interaction with audiences, obtaining feedback, and building stronger trust. Objective, accurate, and balanced perceptions strengthen public participation, encourage better decision-making, and improve understanding of issues.